PALEOZOIC LINKS AMONG SOME ALASKAN ACCRETED TERRANES AND SIBERIA BASED ON MEGAFOSSILS - Blodgett R.B.; Boucot A.J.; Rohr D.M. (My University, 2002)
Biogeographically distinctive Paleozoic fossil biotas from the Farewell terrane (which includes three previously defined subterranes, Nixon Fork, Dillinger, and Mystic) of southwestern Alaska document close ties to Siberia and the Urals. Close ties are especially notable in Middle Cambrian trilobites, Upper Ordovician brachiopods, Upper Silurian brachiopods and aphrosalpingid sponges, Lower Devonian (Emsian) brachiopods, and Permian plants. These biogeographic links suggest that the Farewell terrane most likely represents a continental margin sequence that rifted away from the Siberian continent. Siberian origins are also indicated for other major Alaska terranes (i.e., the Alexander terrane of southeastern Alaska, the Arctic Alaska terrane, and York terrane of northern Alaska) based on their close faunal ties with the Farewell terrane and Siberia. Faunally, the only truly North American part of Alaska is the triangular area within east-central Alaska, bounded roughly by the Porcupine River to the northwest, and the Yukon River on the southwest. Paleozoic faunas from this area are closely similar to those found in Laurentian (North American) miogeoclinal and cratonic strata of northwestern Canada to the east, and are quite distinct from Farewell terrane faunas at the species level throughout most of the Paleozoic.
Keywords: Paleozoic; Paleozoic; Палеозой